The mediation of bond strain by vacancies and displacive disorder in A-site-deficient perovskites. (1st April 2021) - Levin, I.; Krayzman, V.; Playford, H.Y.; Woicik, J.C.; Maier, R.A.; Lu, Z.; Bruma, A.; Eremenko, M.; Tucker, M.G.
Abstract: Local distortions in perovskite-like A-site-deficient (Sr, La)TiO3 solid solutions have been determined by refining large-scale atomic configurations against neutron/X-ray total-scattering and extended-X-ray-absorption-fine-structure data. Structural relaxations in this system are driven by the competing bonding requirements of Sr, La, and the undercoordinated oxygen atoms that surround vacant A-sites, which form upon substitution of La for Sr. La cations exhibit significant, disordered off-center displacements within their oversized oxygen cages required by the larger Sr cations. The resulting split-site probability density distributions of La vary with the Sr/La ratio and the state of the A-site ordering, which together modify the structure's ability to relieve the tensile bond strain around La through octahedral rotation and displacements of oxygens surrounding the vacancies. The displacive disorder of La can provide a hitherto overlooked mechanism for reducing the thermal conductivity, which is relevant to thermoelectric properties of this system. A comparison of the local structural behaviors in (Sr, La)TiO3 and the previously studied (Na, Bi)NbO3 solid solutions permits generalizations about A-site deficient perovskites. We find that A-site vacancies provide the nearest-neighbor oxygens with a degree of freedom to mediate the strain in the system, and their effects on local structural relaxations are determined by cation chemistry and stoichiometry. Graphical abstract: Image, graphical abstract